THE REPUBLIC OF UZBEKISTAN'S INTERNATIONAL EFFORTS TO STABILIZE THE SOCIO-POLITICAL SITUATION IN AFGHANISTAN (Scientific journal of the Fergana State University, 2024)
This article discusses the external policy of the Republic of Uzbekistan regarding the stabilization of the socio-political situation in Afghanistan. It highlights Uzbekistan’s active role, particularly its participation in international conferences and forums on Afghan issues, indicating the country’s favorable foreign policy stance. Additionally, the scholarly work presents prognostic analyses of the positive impact of diplomatic relations on Uzbekistan’s economy, as well as on the international recognition of Afghanistan.